On saving and investing: An experimental study of intertemporal decision making in a complex stochastic environment - Vital Anderhub; Werner Güth; Florian Knust (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The experimental situation presents a complex stochastic intertemporal allocation problem. First, two initial chance moves select one of three possible termination probabilities which then determines whether life lasts 3,4,5, or 6 periods. Compared to Anderhub et al. (1997) participants are allowed to invest into a risky, but profitable asset. We investigate whether the willingness to invest can help to explain saving behavior, i.e. experimentally observed intertemporal decision making.
urn:nbn:de:kobv:11-10047057
Keywords: 330